2016
DOI: 10.1146/annurev-nutr-071715-050916
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Ability to Taste Bitter Thiourea Compounds: Implications for Food Acceptance, Dietary Intake, and Obesity Risk in Children

Abstract: The ability to taste bitter thiourea compounds, such as phenylthiocarbamide (PTC) and 6-n-propylthiouracil (PROP), is inherited. Polymorphisms in the bitter-taste receptor TAS2R38 explain the majority of phenotypic variation in the PROP phenotype. It has been hypothesized that the PROP phenotype is a marker for perception of a variety of chemosensory experiences. In this review, we discuss studies that have investigated the relationship between bitter-taste response and dietary behaviors and chronic health in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 136 publications
(189 reference statements)
4
59
1
2
Order By: Relevance
“…Keller et al 2016 [18] Children incapable of sensing PROP (non-tasters) prefer and ingest dietary fat and are more propense to obesity Choi S. et al…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Keller et al 2016 [18] Children incapable of sensing PROP (non-tasters) prefer and ingest dietary fat and are more propense to obesity Choi S. et al…”
Section: Resultsmentioning
confidence: 99%
“…1994 [40] Cancer treatment can also directly impair the chemosensory processes, thus impairing stimulus transport (e.g., reducing mucus secretion) and modifying transduction mechanisms (non-tasters) prefer and ingest dietary fat and are more propense to obesity [18]. Choi et al [19], using PROP or chili pepper in the test, reported that subjects with a better perception of bitterness had a lower BMI and a lower energy consumption and lipid intake (p < 0.03, p < 0.001 and p < 0.001, respectively).…”
Section: Bitterness Perception and Other Diseasesmentioning
confidence: 99%
See 3 more Smart Citations